PROBLEMATICS OF JINAYAT QANUN IMPLEMENTATION IN NANGGROE ACEH DARUSSALAM COMMUNITY - Zainuddin, Zainuddin; Sahban, Sahban (Tadulako Law Review, 2018)
This paper explores the implementation of jinayat law in the perspective of equality before the law in the people of Nanggroe Aceh Darussalam. Qanun Number 6 of 2014 concerning Jinayah Law is the implementation of Law Number 18 Year 2001 concerning Special Autonomy for the Province of Aceh Special Region as the Province of Nanggroe Aceh Darussalam. Qanun Number 6 of 2014 concerning Jinayah Law. This research is a normative law and is descriptive in nature and the approach used is the law approach, case approach, and conceptual approach. In its application, the Jinayat Qanun has heeded the principle of equality before the law because Jinayat Qanun applies only to certain fingerprints. There are ten prohibited acts (jarimah) in accordance with Islamic Shari'a in the qanun. The clause is khalwat, maisir, and gambling, adultery, the practice of homosexuals (liwath), lesbians (musahaqah) and marital bonding (ikhtilat). In addition, it has not protected women victims of crime, and also discriminates against non-Muslims.